THEORIES OF COST. - Cole, William Morse (The Accounting Review, 1936)
A little examination shows that there must be differences, else not so much difference would occur in the calculation of costs. On the face of it, nothing seems simpler, at least in theory, than knowing what is the cost of anything. Given the elements entering into a thing, its cost, financially expressed, is but the slim of those elements, each financially expressed. When we come to the practical test, as we all very well know, we find that the elements entering into the cost of a thing are not usually given, but have to be learned by analysis, often by almost impossibly fine spun reasoning, and, even in the cases in which the elements are given, a philosophical basis must be found for applying those elements to the case in hand. If an article is produced by a machine run by an operator, we cannot know what the article cost until we know what the operation of the machine cost. Learning that involves an investigation into a host of subsidiary costs like insurance, rent, taxes, fuel, engine-room wages, etc. and some of these elements of cost in but one of the final elements of cost involve in their turn several other analyses of cost into new elements which in their turn may involve others. Yet if we had all these given we should still need a basic theory of cost before we could arrive at our final figure unless, indeed, our case happens to be unusually simple.